NK cells under hypoxia: the two faces of vascularization in tumor and pregnancy - Garcés Lázaro, Irene; Kotzur, Rebecca; Cerwenka, Adelheid; Mandelboim, Ofer (Frontiers in immunology, 2022)
Environmental conditions greatly shape the phenotype and function of immune cells. Specifically, hypoxic conditions that exist within tissues and organs have been reported to affect both the adaptive and the innate immune system. Natural killer (NK) cells belong to the innate immune system. They are among the first immune cells responding to infections and are involved in tumor surveillance. NK cells produce cytokines that shape other innate and adaptive immune cells, and they produce cytolytic molecules leading to target cell killing. Therefore, they are not only involved in steady state tissue homeostasis, but also in pathogen and tumor clearance. Hence, understanding the role of NK cells in pathological and physiological immune biology is an emerging field. To date, it remains incompletely understood how the tissue microenvironment shapes NK cell phenotype and function. In particular, the impact of low oxygen concentrations in tissues on NK cell reactivity has not been systematically dissected. Here, we present a comprehensive review focusing on two highly compelling hypoxic tissue environments, the tumor microenvironment (pathological) and the decidua (physiological) and compare their impact on NK cell reactivity.
Gesehen am 20.12.2022